Ethics of Tourism Guidance Profession in Saudi Arabia - Aati, Abeer Mohammed (Journal of Humanities & Social Sciences, 2020)
The problem of research is the professional sector's need for tour guides that meet all criteria, especially the standard of ethics and good handling of tourists, and the need to show the tourism guidance in accordance with Islamic Sharia. In light of the problem, this study aimed to enhance and improve the tour guide's belonging to his mission and profession, and to contribute to the development of the society in which he lives, and to promote the tourism sector. Also, to motivate guide's in the tourism sector to adhere to the ethics of this profession because of its impact on tourists and the tourism process. To achieve the objectives of the study, the researcher followed integrated approach. The study showed a set of results, the most important of which are: 1. Ethics is the foundation for the progress, prosperity and advancement of nations. 2. The ethics of the tourism guidance profession shall be based on general rules determined by the rules, regulations and laws for practicing them. 3. The general meaning of the ethics of the tourist guiding profession is based on a set of behavioral standards that tour guides use as a reference to guide their behavior during their performance. 4. The main purpose of the profession of tourism guidance in the Kingdom is to pay attention to the seed of tourism, development and work to strengthen the role of the tour guide in it as one of the pillars and important tributaries in spreading information about his country with pride. 5. The greatest civilizational functions that the tour guide should be aware of is the determination of tourism industry success through: assimilation and respect for different cultures, awareness and care of tourism heritage, integrated knowledge of tourist and historical places, and cooperation in the profession of tourist guidance created a specialization of the tour guide during his work, in order to achieve the desired goals of unity and unnecessary community among individuals during work in the tourism sector. 6. The ethics of the tourist guidance profession has an impact on tour guides since it seeks to spread values and cultures between individuals and society, exchanging traditions and principles and acculturate it among them. The researcher recommended the following: establishing university education centers to prepare and form of tourist guide's character ethically. Awareness-raising towards the establishment of professional organizations that monitor the behavior of tourist guides in this profession and help them to continuously develop themselves professionally, culturally and informationally. The need to learn of languages, especially English; because of its profound impact in this profession
Keywords: ethics; profession; tourist guidance; Saudi Arabia